Treatment of psoriasis with topical agents: Recommendations from a Tuscany Consensus. Issue 6 (20th September 2017) - Chiricozzi, Andrea; Pimpinelli, Nicola; Ricceri, Federica; Bagnoni, Giovanni; Bartoli, Laura; Bellini, Mauro; Brandini, Luca; Caproni, Marzia; Castelli, Antonio; Fimiani, Michele; Marsili, Franco; Mazzatenta, Carlo; et al.
Abstract: Psoriasis is a chronic and relapsing inflammatory skin disease, clinically characterized by erythematous and scaly plaques. Treatment approach is mainly driven by disease severity, though several factors should be considered in order to identify the optimal therapeutic choice. Mild psoriasis may be treated with a wide array of topical agents including corticosteroids, vitamin D analogs, keratolytics, and calcipotriol/betamethasone propionate compound. Because guidelines may not provide practical indications regarding the therapeutic approach, the use of topical agents in psoriasis is more individually tailored. In order to homogenize the standard of care, at least in a local setting, we collected the real‐life‐based recommendations for the use of topical therapies from an expert panel, the Tuscany Consensus Group on Psoriasis, representing all leading centers for psoriasis established in Tuscany. With this document, this consensus group sought to define principles guiding the selection of therapeutic agents with straightforward recommendations derived from a real‐life setting.